Mentor Graham correspondence - Graham, Mentor, 1800-1886.
ALS (1 November 1864) from Graham to his brother, Robert W. Graham, concerning voting for Abraham Lincoln in the presidential election of 1864, the secessionists, family members in battle, and life in Springfield, Illinois.
Abraham Lincoln's teacher.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Graham, Robert W., -- active 1864 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Presidents -- United States -- Election -- 1864.; Secession -- Southern States; Springfield (Ill.) -- Social life and customs; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 1861-1865.; Educators